Sentencing in criminal cartel cases in Ireland: The duffy judgement - Paul K. Gorecki; Sarah Maxwell (The Economic and Social Research Institute (ESRI), 2012)
Despite 33 convictions of individuals and firms for criminal cartel offences in Ireland since 1996, there is only one reported judgment. The paper examines the Duffy judgment concerning a member of the Citroen motor vehicle cartel. The judgment provides some guidance on sentencing: cartels are pernicious and jail sentences are to be expected in future cases. However, no guidance is provided as to how the jail term for an individual will be determined or the fine for an individual or a firm. Despite the statement that cartels are pernicious, the fine levied on Duffy Motors was 1.3 per cent of the maximum fine under competition legislation and 1.1 per cent of the likely increase in profits due to firm's participation in the cartel. An alternative approach to sentencing is suggested that utilises a well developed methodology and is consistent with the view that cartels are pernicious, while at the same time leaving considerable judicial discretion in determining the ultimate sentence.
Keywords: 330